Harmonics issues of three-phase diode rectifiers with a small DC link capacitor - Zare, Firuz (2014)
© 2014 IEEE. This paper presents effects of DC link capacitor sizes in a three phase diode rectifier on input current harmonics at a system level. A small DC link capacitor generates a resonant frequency with a line inductor which can affect and increase the input current harmonics. According to IEC 61000-3-2 and IEC 61000-3-12 standards, low order current harmonics of a power electronic system should be controlled below a certain limits but at a power system level, voltage harmonics are important and should be reduced. SABER simulations have been carried out for a three phase motor drive system with different DC link capacitors and at different power levels in order to analyze the input current harmonics and the power quality of the power network.